PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, LEVERAGE TERHADAP MANAJEMEN LABA DI PERUSAHAAN MANUFAKTUR - Edward Ellyas Kussubagio; Agustin Ekadjaja (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This study was conducted to determine the extent to which the influence of firm size, profitability and leverage on earnings management variables as the dependent variable. Sampling was carried out in this study using a purposive sampling method which resulted in a total of 33 manufacturing companies with basic and chemical or cement industrial subsectors listed on the Indonesia Stock Exchange (IDX) in the 2016-2019 period. This study uses secondary data in the form of financial statements as a source of data collection and processed using the Eviews 10 program. The results of this study indicate that company size has a negative and significant effect on earnings management, profitability does not have a significant effect on earnings management and leverage has a significant effect on earnings management. positive and significant to earnings management.